Code Mixing of A Podcast Conversation between Two Indonesian Celebrities: A Sociolinguistics Study - Sakti Oktavia; Meita Lukitawati Sujatna; Bagus Tri Saputra Nanda (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The goals of this study are to: (1) specify the various types of code-mixing; and (2) discuss the factors that affect code-mixing. The descriptive analysis method is the one that is employed. The procedures involved in gathering data are viewing, creating scripts, identifying, categorizing, and analyzing the discussions seen in the video, as well as drawing conclusions about the findings. Muysken's notion of code-mixing served as the foundation for this investigation. There are three types of code-mixing, including insertion, alternation, and congruent lexicalization, according to Muysken's theory (2000:3; 2006: 152-153). The analysis's findings revealed that Alternation (81 data), Insertion (78 data), and Congruent Lexicalization are the three most common types of code-mixing (28 data). The three types of code-mixing were examined using the qualitative descriptive methodologies. Seven additional explanations for code-mixing have been established based on Hoffmann theory (1991). Speaking about a specific subject, quoting another person, emphasizing something (expressing solidarity), interjecting (inserting sentence fillers or sentence connectors), using repetition for clarification, wanting to make the speech's content clear for the listener, and expressing group identity are all examples of these behaviors. Repetition used for clarification is the most frequently used justification for code-mixing.